Antinomy of Intellectual Property Right, Human Right to Health and Health Development in Indonesia - KRISTHY, Mutia Evi; NOOR, Syamhudian; SILAM, Achamad Adi Surya Guntur; HAREFA, Fidelis; RASAU, Noel de Paulo (Indonesia Strategic Sustainability, 2025)
This study examines intellectual property rights, human rights to Health, and health development in Indonesia after COVID-19. In this study, the type of research used is normative legal research using legal material collection techniques in document studies or literature studies. The approach used in this study is statutory, and the sources of legal materials used are primary, secondary, and tertiary. The results showed that Health is a fundamental need of every individual, family, and society, which the Constitution protects. The founders of the Unitary State of the Republic of Indonesia (NKRI) also understood the importance of Health for the life of the nation and state. Health efforts in Indonesia adopt a modern health and medical system whose user community background is Western socio-cultural. On that basis, there are many obstacles to developing health care and treating and healing diseases when served to the people of Indonesia. Health is a subsystem of National Resilience because it must involve other subsystems through interaction, interrelation, interdependence, and independence to achieve national Health.